2017
DOI: 10.11124/jbisrir-2017-003375
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, experiences and preferences of patients receiving a clinician's touch during intimate care and procedures: a qualitative systematic review

Abstract: The synthesized finding from this review suggests that:More research is needed to explore the perceptions and preferences for intimate touch among diverse populations, generations, cultures and contexts. Particular exploration is needed for populations with additional vulnerabilities to misunderstandings, anxiety and abuse, such as pediatric and geriatric patients, and patients with physical, mental and cognitive impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…The results of studies in various countries with different religions and cultures showed that most patients had a moderate or negative attitude toward receiving care from an opposite-gender nurse and preferred the same-gender nurse to care for them 22,32,33 which can be due to feelings of ashamed and anxious while being touched or examined by an opposite-gender nurse. 25,34 The results of Duman's study 32 in Turkey demonstrated that female patients had a negative attitude toward the opposite-gender nurses, and none of them were willing to take care of nurses of the opposite gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of studies in various countries with different religions and cultures showed that most patients had a moderate or negative attitude toward receiving care from an opposite-gender nurse and preferred the same-gender nurse to care for them 22,32,33 which can be due to feelings of ashamed and anxious while being touched or examined by an opposite-gender nurse. 25,34 The results of Duman's study 32 in Turkey demonstrated that female patients had a negative attitude toward the opposite-gender nurses, and none of them were willing to take care of nurses of the opposite gender.…”
Section: Discussionmentioning
confidence: 99%
“…The scores ranged between 21 and 63, while a higher score indicated more positive attitude. The overall score was divided into three levels of negative (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), moderate (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), and positive attitude (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). The scoring of the third to seventeenth questions was done inversely.…”
Section: Methodsmentioning
confidence: 99%
“…The nursing care routines are task-oriented, aimed at promoting physical and psychological comfort where touch is essential and unavoidable (Pedrazza et al 2018 ). Nurses touch patients when performing care procedures such as assistance with intimate bodily functions such as bathing and elimination (toileting), communicating care and ensuring comfort (Kelly et al 2018 ; O’Lynn, Cooper & Blackwell 2017 ). Physical touch requires sensitivity, responsiveness and involvement from a nurse as it implies physical, cognitive and emotional proximity to the patient (Pedrazza et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nursing students have to touch a patient’s body, and a patient allows a stranger to see and touch his or her fragile body. Provision of intimate care may produce feelings of discomfort, anxiety, or fear and might be misinterpreted as having sexual intent (O’Lynn et al 2017 ). Thus, nurses are constantly required to negotiate boundaries and spaces (Kelly et al 2018 ) during patient care to avoid discomfort for both parties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation